FRI0069 Neutrophils play a key role in the regulation of the chronic inflammation associated with rheumatoid arthritis through epigenetic mechanisms modulated by anti-ccps antibodies and reversed by biologic therapies. (15th June 2017) - Ruiz-Limon, P; Rosa, I Arias de la; Abalos, MC; Perez-Sanchez, C; Jimenez-Gomez, Y; Caracuel, M; Calvo, J; Ortega, R; Castro, M; Collantes, E; Escudero, A; Lopez-Pedrera, C; et al.
Abstract : Background: MicroRNAs (miRNA) are as a new class of modulators of gene expression, regulating inflammation, degradation of extracellular matrix and invasive behavior of the resident cells in rheumatoid arthritis (RA). Objectives: 1) To investigate the miRNA expression profile in synovial and blood neutrophils in RA and its role in the pathogenesis of this disorder. 2) To study the effects of biological therapies on the miRNA profile in neutrophils. Methods: Neutrophils were isolated from peripheral blood (PB) of 25 healthy donors (HD) and 25 RA patients. Neutrophils were isolated from paired synovial fluid (SF) of 15 RA patients. nCounter microRNA Assay was used to detect 800 human microRNAs simultaneously. Altered miRNAs were analyzed for potential mRNA targets using Ingenuity pathways analysis (IPA) software. mRNA targets and genes involved in miRNA biogenesis were evaluated. RA neutrophils were treated in vitro with tocilizumab and infliximab.Healthy neutrophils were treated in vitro with anti-CCPs isolated from RA patients alone or combined with tocilizumab or infliximab. RA neutrophils were cotransfected with the pre-miRNAs 126 and 148. Results: 94 miRNAs were downregulated and 3 upregulated in PB neutrophils from RA patients compared to HD.Among the miRNAs deregulated in blood, 34 miRNAs were even more significantly reduced in SF neutrophils. Accordingly, RA neutrophils showed a downregulation of the proteins participating in miRNA biogenesis and upregulation of its mRNA targets. Altered miRNAs were mainly involved in immunological disease and inflammatory response, suggesting the abnormal activation of this cell subtype in RA. In vitro treatment of RA neutrophils with infliximab reversed the expression of miRNAs, genes involved in their biogenesis and reduced the inflammatory profile in these cells.In addition, treatment of healthy neutrophils with IgGs anti-CCPs isolated from RA patients decreased the expression of the miRNAs, proteins involved in the biogenesis machinery and increase its inflammatory targets. Finally, cotransfection of RA neutrophils with the pre-miRNAs 126 and 148 reduced the levels of their target proteins. Conclusions: 1)RA neutrophils exhibit a defect in the miRNAs processing, showed by a decrease in most of the detected miRNAs and the downregulationof proteins involved in their biogenesis. This defect seems to be modulatedby anti-CCPs antibodies.2)miRNA downregulation is even more pronounced in synovial fluid neutrophils, which may contribute to the high inflammatory profile of these cells in the joint. 3) Infliximab reverses the altered miRNA profile and the defect in the biogenesis machinery, reducing the proinflammatory pattern in these cells. 4)miRNAs 126 and 148 regulate the expression of numerous inflammatory proteins in RA neutrophils.In sum, this study shows that the neutrophils play a key role in the regulation of the chronic inflammation link to RA. The effect, associated to epigenetic mechanisms, seems to be mediated by the anti-CCPs and is reversed by biologic therapies. Acknowledgements: Funded by CTS7940, PI2013–0191, ISCIII (CP15/00158, PI15/001333), RD16/0012/0015 Disclosure of Interest: None declared